Wzorując się na tym sposobie wyznaczania par liczb wyznacz pięć par liczb spełniających podane równanie.

Przykład: 2x - 4y + 5 = 0 I -5+4y
2x=-5 + 4y I :2
X= -2,5 + 2y
dla y= 1
x = - 2,5 +2*1 -0.5
itd.


a) x-5y-4=0
b) -3x+y=6
c) ½x+4=3y














1

Odpowiedzi

2010-04-12T00:35:44+02:00
A) x-5y-4=0
x=5y+4

y=-4
x=5*(-4)+4
x=-20+4
x=-16

y=-2
x=5*(-2)+4
x=-10+4
x=-6

y=0
x=5*0+4
x=4

y=1
x=5*1+4
x=9

y=3
x=5*3+4
x=15+4
x=19

{-4;-16},{-2;-6},{0;4},{1;9},{3;19}

b) -3x+y=6

-3x=6-y |:(-3)
x=1/3y-2

y=-4
x=1/3*(-4)-2
x=-4/3-2
x=-3 i 1/3

y=-2
x=1.3*(-2)-2
x=-2/3-2
x=-2 i 2/3

y=0
x=1/3*0-2
x=-2

y=1
x=1/3*1-2
x=1/3-2
x=-1 i 2/3

y=3
x=1/3*3-2
x=1-2
x=-1

{-4;-3i1/3},{-2;-2i2/3},{0;-2},{1;-1i2/3},{3;-1}

c) ½x+4=3y |*2
x+8=6y
x=6y-8

y=-4
x=6*(-4)-8
x=-24-8
x=-32

y=-2
x=6*(-2)-8
x=-12-8
x=-20

y=0
x=6*0-8
x=-8

y=1
x=6*1-8
x=6-8
x=-2

y=3
x=6*3-8
x=18-8
x=10

{-4;-32},{-2;-20},{0;-8},{1;-2},{3;10}


1 3 1